Transformasi Kompetensi Guru BK: Optimalisasi Soft Skill dan Hard Skill untuk Penguatan Keterampilan Siswa di Kota Payakumbuh - Fikri, Miftahul; Putra, Ade Herdian; Arafani, Adnan; Adlya, Soeci Izzati; Handani, Tri; Syahri, Lia Mita (Counseling and Humanities Review, 2025)
This community service activity aimed to strengthen the competence of guidance and counseling teachers in Payakumbuh City through training on the use of Curipod as an innovative interactive platform in counseling services. The program was designed to optimize the balance between soft skills such as empathy, communication, collaboration, and creativity, and hard skills including the mastery of digital technology, program design, and data-based planning. The activity was carried out in the Hall of the Payakumbuh City Education Office and involved guidance and counseling teachers from various schools. The training included the introduction of Curipod features, practical sessions in designing counseling scenarios, and reflective discussions to integrate interactive technology into counseling services. The results showed a significant improvement in teachers’ skills in operating Curipod, designing creative service scenarios, and presenting materials interactively, as assessed by the service team. The training also enhanced teachers’ confidence and encouraged them to adopt more innovative approaches in counseling practices. These findings confirm that Curipod can be an effective medium to support creative counseling services that are relevant to the characteristics of the digital generation. The implication of this program is the need for continuous training and institutional support to ensure the sustainable implementation of interactive technology in school counseling services.